원자력안전규제기관에 관한 비교 검토 -IAEA 규범과 비교를 중심으로 - 차성민 (한국비교정부학보, 18(3), 2014)
The regulatory body must be structured in such a way as to ensure that it is capable of discharging its responsibilities and carrying out its functions independently, effectively and efficiently. One of the most important attributes of a regulatory body is its independence from interference in its regulatory functions. This idea has been developed in a number of IAEA documents and in relevant international conventions. The requirements are reviewed in this paper relate to the organization of the regulatory body: its structure, allocation of resources, coordination with other governmental authorities, management system, staffing, and relationship with advisory bodies under the IAEA laws. This paper is also analyzed general requirements for performing the functions of the regulatory body to preserve the consistency and stability of operations and constructive liaison with authorized parties, comparing the IAEA laws and Korean laws of nuclear safety. As a result, key point was derived. That is the regulatory body shall perform its functions in a manner that does not compromise its effective independence. And legal policy of supplementation is proposed in this article. KCI Citation Count: 4